The “questionnaire of the difference imaginary baby vs. real baby”: a new instrument for the evaluation of differences between prenatal and postnatal maternal perceptions after delivery - Carolina Santos Chagas; Patrícia Mendes Lourenço Maltez; Sandra Isabel Santos Miranda; João Manuel Rosado de Miranda Justo (INFAD, 2015)
INTRODUCTION: Fantasmatic baby, imaginary baby and the real baby are important concepts for the understanding of the psychological life of pregnant women as of newly mothers.